Analisis Kinerja Perangkat Desa Dalam Melakukan Pelayanan Administrasi Pada Kantor Desa Pinayungan - Ega Fatimah; Syifa Pramudita Faddila (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to analyze the performance of village officials in providing administrative services at the Pinayungan village office. Functional and functional administrative services are important factors in meeting the administrative needs of village communities. Direct observation, interviews and documentation studies are used as research methods to collect information about the performance of village officials and the implementation of administrative services. Performance analysis considers, among other things, service speed, data accuracy, responsiveness to public requests, and adherence to established administrative procedures. The results of the study show that even though there are deficiencies in administration, village officials at the Pinayungan Village Office as a whole are quite good at carrying out administrative tasks. However, to increase the effectiveness and efficiency of administrative services in the future, several suggestions for improvement have been made. This study is expected to contribute to the improvement of the administrative service system at the village level and to become a reference for the local community in optimizing the activities of village officials.